The effect of frequency selective fading on wireless indoor network - Lee, Chyan (2011)
The emerging of wireless indoor network could reshape our communication with others. There are two classes of networks: (1) Narrowband application, such as paging or wireless PABX to transmit voice and low rate data and (2) Wideband application, such as wireless Local Area Network capable of handling data rate up to several Megabits per second This research project is to determine the factors that limit the transmission of wideband data in an indoor radio channel.